Cold Signaling and Cold Response in Plants - Kenji Miura (International Journal of Molecular Sciences, 2013)
Plants are constantly exposed to a variety of environmental stresses. Freezing or extremely low temperature constitutes a key factor influencing plant growth, development and crop productivity. Plants have evolved a mechanism to enhance tolerance to freezing during exposure to periods of low, but non-freezing temperatures. This phenomenon is called cold acclimation. During cold acclimation, plants develop several mechanisms to minimize potential damages caused by low temperature. Cold response is highly complex process that involves an array of physiological and biochemical modifications. Furthermore, alterations of the expression patterns of many genes, proteins and metabolites in response to cold stress have been reported. Recent studies demonstrate that post-transcriptional and post-translational regulations play a role in the regulation of cold signaling. In this review article, recent advances in cold stress signaling and tolerance are highlighted.